Negotiating Transcendentalism, Escaping « Paradise » : Herman Melville’s Moby-Dick. - Ramón Espejo Romero (European Journal of American Studies)
By reviewing the critical literature on Melville and Transcendentalism and then undertaking a close reading of Moby-Dick (1851), this paper argues that the novel reflects, among other things, an ongoing debate between the novelist and Transcendentalist philosophy. While in later works, Melville seems to express a more robust condemnation of the Concord movement and its dangerous idealism, Moby-Dick occupies less firmly-defined territory. The Transcendentalist urge of an Ahab to be himself is a counterpoint to Ishmael’s more idiosyncratic deployment of self-reliance, communion with the oversoul, and various other concepts easy to trace back to Emerson or Thoreau. The conclusion seems to be that a negotiation is necessary if Transcendentalism is to be heeded at all, precisely the kind of negotiation Ishmael undertakes throughout the novel, one which spares him from the maelstrom created by a more radical approach to self-acceptance and self-fashioning.